2016
DOI: 10.1590/0037-8682-0440-2015
|View full text |Cite
|
Sign up to set email alerts
|

Number of leprosy reactions during treatment: clinical correlations and laboratory diagnosis

Abstract: Introduction:The occurrence of leprosy reactions, a common event during treatment, may be mostly related to the action of multidrug therapy on Mycobacterium leprae. The clinical and laboratory monitoring of patients with reactions is important, since collecting data that assists in predicting the risk of reactions may help to prevent disability. Methods: This was a sectional study, in order to correlate clinical and laboratory diagnosis with the number of reactions during treatment. Spearman's correlation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 13 publications
2
16
1
6
Order By: Relevance
“…Higher levels of anti-LAM in the leprosy reaction group is due to the presence of great number of individuals with ENL, since LAM is involved in the formation of immune complexes and in the pathogenesis of erythema nodosum leprosum [39]. High levels of anti-PGL-I in leprosy reactions, independently on the type of reaction, ratify that this antigen is a risk marker for the occurrence of reactions, during treatment and after discharge from MDT, corroborating with previous studies that showed positive serology anti-PGL-I as a risk factor to the reactional condition [3, 7, 40].…”
Section: Discussionsupporting
confidence: 82%
“…Higher levels of anti-LAM in the leprosy reaction group is due to the presence of great number of individuals with ENL, since LAM is involved in the formation of immune complexes and in the pathogenesis of erythema nodosum leprosum [39]. High levels of anti-PGL-I in leprosy reactions, independently on the type of reaction, ratify that this antigen is a risk marker for the occurrence of reactions, during treatment and after discharge from MDT, corroborating with previous studies that showed positive serology anti-PGL-I as a risk factor to the reactional condition [3, 7, 40].…”
Section: Discussionsupporting
confidence: 82%
“…Dynamic and unpredictable episodes of increased inflammation, leprosy reactions, can occur before, during and even after treatment, with a higher likelihood to occur in adults than in children 9,10 . These immunological complications are the principal cause of leprosy-associated irreversible neuropathy and are experienced by 30–50% of leprosy patients one or more times, mostly in the unstable borderline lepromatous patients with substantial bacterial loads 11 . Two types of reactions are recognized: reversal reactions or type 1 (RR) and erythema nodosum leprosum (ENL).…”
Section: Introductionmentioning
confidence: 99%
“…These result from changes to the immune balance between the host and M . leprae that lead to increased morbidity and impairment of peripheral nerve function [7, 8, 9].…”
Section: Introductionmentioning
confidence: 99%